'Landing' salmon aquaculture: Ecologies, infrastructures and the promise of sustainability. Issue 123 (July 2021) - Martin, Sarah J.; Mather, Charles; Knott, Christine; Bavington, Dean
Abstract: In this paper, we critically assess two key shifts in the global salmon aquaculture sector: first, the development of large land-based salmon production facilities and, second, the increased reliance on land-based commodity crops in salmon feed. Proponents of this 'landing' of salmon aquaculture's infrastructure promise sustainable solutions to the environmental challenges of farming in and from the sea. But the firmness of land is no predictor of a given or stable form of capital accumulation, nor does it represent a straightforward 'sustainable solution' to the ecological challenges in conventional salmon farming. We show how productive and speculative capital underpin these new projects, but also how these projects meet varied frictions which raises questions about whether 'landing' infrastructures represents a sustainable alternative to conventional salmon aquaculture. We explore this development in the context of recent debates on infrastructures as they relate to environments, ecologies and the nonhuman. We argue that analysing industrial aquaculture, and more broadly industrial animal agriculture, through the lens of environmental or ecological infrastructures, helps to bring into focus the massive and global infrastructuring of nature and nonhumans. In turn, we are able to illuminate the political, social and ecological implications of the industrial containment and feeding of animals. This article contributes to the emerging field of scholarship on ecological infrastructures by critically assessing the landing of salmon in response to the socio-ecological crisis in conventional salmon aquaculture.